Urgensi Toleransi Antar Agama dalam Perspektif Tafsir al-Syaârawi - M. Thoriqul Huda; Uly Dina (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2019)
Al-Qur'an is a Muslim holy book which regulates all human life. Not only set the way of life, but the Qur'an is the life of the Muslims themselves. Each verse in the Qur'an contains complete, perfect, and comprehensive messages. Both of the verses are global and even specific. The contents of the Qur'an in regulating human life not only discuss one dimension, but are very multi-dimensional, among them dimensions in theology, bermuamalah, worship, and so on. Muslims and non-Muslims in interacting socially have boundaries that have been arranged in the Qur'an. Tolerant values ​​are explained in Q.S. al-Baqoroh: 256. This article about the concept of tolerance in the Qur'an, that in terms of worship and aqeedah there is no tolerance. Because in terms of aqeedah that is absolute. Therefore, cases that can injure aqeedah should be avoided. The context of tolerance between religions here is free to worship according to the beliefs of each. There is no mutual prohibition in carrying out their worsip. Tolerance will overestimate mutual respect and cooperation between religious communities. Religious tolerance causes believers in God. Different people can live and coexist with each other safely and peacefully so that harmony is created. In understanding verses in the Qur’an well, then the interpretation is the main key to achieving it. At the end of the 20 Mcentury an exegete from Egypt was born. He is Imam Mutawalli al-Sya’rawi with a wll known interpretation of Sya’rawi.